Building Resilience in Students with Learning Disabilities: A Strength-Based Approach - saini, Preeti (Innovative Research Thoughts, 2017)
The educational system is changing to accommodate students with learning difficulties, who have their own set of talents and abilities that may be used to forge resilience and take charge of their own education. advocates for a strength-based approach to fostering resilience in students with learning difficulties and the concept of resilience. Educators and support systems can help these adolescents overcome obstacles, gain valuable life skills, and succeed in school if they reframe the conversation from one of weakness to one of strength. intellectual, social, and emotional difficulties that students with learning disabilities often experience. the idea of resilience, emphasising its value in fostering success and happiness in spite of setbacks.